Enabling Stable High‐Voltage LiCoO2 Operation by Using Synergetic Interfacial Modification Strategy. (3rd September 2020) - Yang, Xuerui; Lin, Min; Zheng, Guorui; Wu, Jue; Wang, Xianshu; Ren, Fucheng; Zhang, Wenguang; Liao, Ying; Zhao, Weimin; Zhang, Zhongru; Xu, Ningbo; Yang, Wanli; et al.
Abstract: Structural and interfacial instability of the LiCoO2 cathode under a voltage exceeding 4.5 V (vs Li/Li + ) severely hinders its practical applications for high‐energy‐density lithium batteries. Herein, a modified electrolyte with nitriles (suberonitrile or 1, 3, 6‐hexanetricarbonitrile) and fluoroethylene carbonate (FEC) coadditives is demonstrated to form an ultrathin and uniform interface layer on LiCoO2 cathode under a synergetic effect. As such, LiCoO2 /Li cells display excellent cyclability at a cutoff voltage of 4.6 V with a capacity retention over 72% after 300 cycles and 60% after 200 cycles at 30 and 55 °C, respectively, even achieving operation at a high current rate (10 C) upon 500 cycles as compared to the controls with fast‐falling capacity to zero. Furthermore, an adsorption‐coordination mechanism between nitriles and cobalt and synergetic effect of coadditives are explored by the alliance of spectroscopic analysis and theoretical calculations. The contributed lone‐pairs on the N 2p orbital of nitriles in coordination lowers the real oxidation state of Co 3+/4+ so that it decreases its catalysis on electrolytes, and the synergy from nitrile‐derived species regulates FEC to form an LiF‐containing electron‐insulated interface layer. This work shares a new insight to nitriles with the synergy of coadditives and paves a way to refine (ultra)high‐voltage LiCoO2 cathode for high‐energy‐density energy storages. Abstract : With fluoroethylene carbonate and nitriles coadditives, a superexcellent cathode electrolyte interphase film with a matrix of CoNCR, LiOCO2 RFCN, [COCH2 ] n, and appropriate LiF species can be endowed, which is resistant to the violent oxidation decomposition of electrolyte at (ultra)high voltage (4.6 V, vs Li/Li + ) and guarantees the structural integrity of cathode materials.